Practical Strategy Understanding English Reading Comprehension - Muallim, Muajiz; Hasanah, Nurul (DEDIKASI PKM, 2024)
English reading comprehension is an important skill needed in various areas of life. However, many students have difficulty understanding English reading. This article is the output of community service activities which aims to discusses several practical strategies that can help improve English reading comprehension. The strategies comprise skimming, scanning, word-attack skills, vocabulary building, interpreting reference, recognizing text-organization and inferencing. The methods used are lecture, discussion, and direct practice. The participants are 30 students of Madrasah Aliyah Negeri (MAN) 2 Parepare who are members of the School English Meeting Club. The results of this community service are (1) increasing students' reading comprehension text skills, (2) increasing participants' awareness of the importance of reading skills, (3) students who are competent in understanding reading comprehension texts.